Political Rights of Former Convicts Perpetrators of Sexual Violence Against Children Positive Legal Perspective and Siyasah Fiqh - Zulfa Almira,; Irwansyah, (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
The political explanation of citizens' rights is regulated in Articles 26D paragraph (3), which states that every citizen has the right to equal opportunities in government. The 1945 Constitution of the Republic of Indonesia, Chapter XA of Human Rights Articles 28A to 28J, regulates the implementation of the political rights of the people in Indonesia. The detailing of the issue in this exploration is the way to repudiate political freedoms for ex-convicts of sexual brutality in light of regulations and guidelines and considered according to the point of view of fiqh siyasa shari'iyah, strategy research that is utilized with Regularizing Purview, the consequences of the conversation got, that the disavowal of Political Privileges for convicts who carry out sexual savagery in Indonesia doesn't struggle with the Lawbreaker Code and Basic liberties, fiqh siyasa syari'iyah advances benefit as well as security for the whole ummah, where the public authority is It is reasonable to give extra discipline as a hindrance for culprits to perpetrate wrongdoings once more.